(untitled) (Revista Internacional de Folkcomunicação, 2024)
The article is part of the field of folkcommunication, more specifically in the information leaflets of cordel literature. The article preliminarily measures the proportion of leaflets from private and public initiatives in a sample of copies that address the theme of illness/health. The article analyzes the content of leaflets that deal with the topic of dengue, its prevention and treatment, admitting, as a hypothesis, that the narratives presented in these leaflets increase the dissemination of the same content disseminated by public communication, among the reading public or listeners of cordel literature.